2012
DOI: 10.1016/j.mineng.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Bench-scale flotation of chrysocolla with n-octanohydroxamate

Abstract: Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, Atomic absorption spectroscopy (AAS) and X-ray Photoelectron spectroscopy (XPS) have been employed to characterise the surface layer and compound formation during the interaction of n-octanohydroxamate with chrysocolla and malachite surfaces. The flotation response of a single mineral chrysocolla -quartz sand sample and mixed chrysocolla -malachite -quartz sand sample using n-octanohydroxamate collector have been investigated. Recoveries of 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…These chelating collectors, such as 1-phenylthiosemicarbazide and potassium octyl hydroxamate, can be used to change the contact angle of the chrysocolla's surface [13]. Hope et al [14,15] also confirmed that n-octanohydroxamate can act as a collector because the formation of multiple layers of copper hydroxamate can result in good chrysocolla recovery. These collectors exhibit superior affinities for copper oxide minerals, but their poor selectivity for gangue minerals and the expensive reagents restrict their industrial application.…”
Section: Introductionmentioning
confidence: 98%
“…These chelating collectors, such as 1-phenylthiosemicarbazide and potassium octyl hydroxamate, can be used to change the contact angle of the chrysocolla's surface [13]. Hope et al [14,15] also confirmed that n-octanohydroxamate can act as a collector because the formation of multiple layers of copper hydroxamate can result in good chrysocolla recovery. These collectors exhibit superior affinities for copper oxide minerals, but their poor selectivity for gangue minerals and the expensive reagents restrict their industrial application.…”
Section: Introductionmentioning
confidence: 98%
“…Chrysocolla interacts well with the sulfhydryl collectors commonly used for copper sulfide flotation, but floats only poorly or very slowly. Research efforts have been made to improve the flotation of chrysocolla [10][11][12][13][14]. Banza and Gock obtained covellite (CuS) and sodium silicate via mechanochemical reaction between chrysocolla and sodium sulfide [15].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidized copper ores are found in silicate or carbonate forms (Hope et al, 2012), malachite being a typical oxide mineral of zinc. Flotation is the commonly used method for beneficiation of malachite and other oxidized copper minerals (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%